Keragaan Pertumbuhan Tanaman Kopi New Planting Sistem Intensifikasi Berkelanjutan - Evizal, Rusdi; Prasmatiwi, Fembriarti Erry (JURNAL AGROTROPIKA, 2024)
Coffee establisment including new planting and replanting is an important effort for sustainable coffee production. This research aims to determine the growth performance of coffee establishment that implement a sustainable intensification system. This research uses survey methods and field experiment. The survey was carried out by interviewing coffee farmer respondents who were obtained randomly from farmer groups in Tanggamus. The field experiment was carried out in the demonstration plot of the Makmur Farmers Group, Sidomulyo Village, Air Naningan District, Tanggamus Regency. The land used is land clearing of an old cocoa plantation, by tilling the land twice using a tractor, using superior local seeds, setting plant distances using a hedge system, applying biochar, planting intercrops and planting shade trees. From the survey results, it can be concluded that coffee farmers apply the principles of sustainable intensification in coffee planting, namely planting coffee with a hedge system, intercropping with annual crops and bananas, and applying soil amendments, especially coffee skin waste and manure. The results of the plot experiment concluded that corn intercropping with tillage at the beginning of coffee planting gave good yield in 2 planting seasons while in the third season productivity decreased greatly. The long dry season is the main obstacle in coffee establisment, includes causing plant death and inhibiting plant growth which is showed by wavy and closing leaves, yellowing leaves, malformed young leaves, and wilting leaves. Cultivating corn plants between row of 2 years old coffee does not affect the vegetative or generative growth of coffee. It does not inhibit the growth of coffee plants as indicated by plant height, number of primary branches, length of primary branches, stem diameter, number of nodes per primary branch, and number of flower bunch per tree. Key words: Coffee, sustainable intensification, new planting, symptoms, yellowing leaves, wilting